Evaluación Dasométrica De Una Plantación De Pinus Radiata D. Don En El Sector San Andrés, Guano, Ecuador - Calva, Miguel Angel Guallpa; Haro, Sonia Carmita Rosero (European Scientific Journal, ESJ, 2018)
There are scarce information concerning the growth and productivity of the trees of the plantation of Pinus radiata D. Don. This is usually found in the forest estate of the Haro-Maderas factory in a condition of soil with sandy loam texture, deep and moderately fast drainage, pH 6.7, fertility between low and high with the specific application of a pruning activity at the age of 5 years, and gradual monitoring every year until 8 years of age. This is considered as part of its management which constitutes a benchmark in the Tahuala sector. For this reason, this study aims to evaluate its forest mass. Circular plots of 8.92m radius were installed at an intensity of 4.33% ha-1 . This, however, is done through a systematic aligned sampling for the collection of dasometric information. The application of statistical estimators showed an altitude of 3145 masl. It reached an average total height of 12.76 m, a DAP of 15.27 cm, the total average tree-1 estimated volume of 0.16 m3 , and its projected value of 303.56 m3 ha-1 . The relationship between the DAPage variables and the average-age total height was high and significant. It has a correlation coefficient equal to 0.99, whose estimation was better with the linear type equation. It was suggested that thinning should be carried out with an intensity of 28.77%. In regards to the remaining trees, it will be very necessary to apply the silvicultural treatment of pruning.